PERSEPSI MAHASISWA PGSD TERHADAP IMPLEMENTASI KKNI DI UNIVERSITAS NEGERI MEDAN - Faisal Faisal (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2018)
This study aims to describe the perception of PGSD students on the implementation of KKNIbased curriculum at Medan State University (Unimed). The research study focused on the implementation of 6 KKNI tasks, namely: routine task, Critical Book Report (CBR), Critical Journal Review (CJR), idea engineering, project, and mini research. This research is a descriptive quantitative research, by taking sample of research from Unimed student of PGSD as much as 240 people. Data were collected by using observation and questionnaire, then analyzed by using descriptive statistic. Outcomes resulting from the results of this study include: (1) research reports that contribute to the direction of policy courses and faculty in running KKNI in the future, (2) national journals with ISSN online that contribute to the development of science, especially related with the implementation of KKNI in Higher Education, and (3) recommendation of institutional policy toward the implementation of KKNI in the future. The result of the research shows that the perception of PGSD students on the implementation of KKNI is 3.33 (83.25%) with Good category. That is, PGSD students have a good perception on the implementation of KKNI in Universitas Negeri Medan.  Keywords : perception, PGSD, curriculum, KKNI